Passivity-Based Control for Transient Power Sharing and State of Charge Restoration in a Semi-Active Supercapacitor-Battery System - Fabian Fracica-Rodriguez; Manuel Acevedo-Iles; David Romero-Quete; Wilmar Martinez; Camilo A. Cortes (Batteries)
This paper presents a passivity-based control (PBC) approach integrated with filtering for a supercapacitor (SC) in a semi-active hybrid energy storage system. The PBC is designed as a current controller using the reference provided by the filter to regulate the system’s load current. Additionally, an external loop is employed to regulate the SC voltage to a desired value. In this external loop, a low-pass filter is included to decouple voltage and current control during instantaneous changes in load. A detailed, step-by-step description of both the PBC and the SC voltage control strategy is provided, illustrating how voltage regulation is effectively decoupled from current control to ensure optimal operation during load transients. The effectiveness of the proposed control strategy is validated through simulations and Power Hardware-in-the-Loop testing under variable current loads. This comprehensive evaluation method enables testing of control strategies in scenarios closely resembling real-world applications.